2012
DOI: 10.1155/2012/539073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Falls and Its Associated Factors among Elderly Diabetes in a Tertiary Center, Malaysia

Abstract: The purpose of this study is to determine the prevalence of falls and its associated factors among elderly diabetes type 2 patients attending a tertiary center in Malaysia. We conducted a cross-sectional study among 288 elderly diabetes type 2. The data collected includes data on sociodemographic, diabetes history, comorbid diseases, drug use, and activity of daily living (Barthel's index). The patient also was examined physically, and balance and gait assessment was carried out. Prevalence of falls among elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
4
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 22 publications
(50 reference statements)
4
49
4
1
Order By: Relevance
“…Prior cross-sectional studies have shown that OH is associated with history of falls among older adults 8,10,24 with few exceptions. 25 However, prospective studies examining this relationship are small, of short duration, and inconsistent with some showing OH to be associated with risk of falls [26][27][28][29][30] and others showing no association.…”
Section: Discussionmentioning
confidence: 96%
“…Prior cross-sectional studies have shown that OH is associated with history of falls among older adults 8,10,24 with few exceptions. 25 However, prospective studies examining this relationship are small, of short duration, and inconsistent with some showing OH to be associated with risk of falls [26][27][28][29][30] and others showing no association.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies conducted by the researchers, Azidah et al and Yeong et al found that the age group of more than 75 years of age gave the highest percentage of falls as compared to the other age groups, with the percentage of 37.5% and 30.3% respectively. 3,4 However, it is also worth mentioning that the results are not statistically significant. And it is further asserted that older adults are prone to falls largely due to the decline of physical, cognitive and affective capacities.…”
Section: Introductionmentioning
confidence: 89%
“…Balance is one of the major factors which associated with falls in the elderly population. Falls are defined as unintentionally coming to the ground or some lower surface and not as a consequence of sustaining a violent blow, loss of consciousness and sudden paralysis as in a stroke incident or epileptic seizure [6]. Falls are a major problem in the elderly because they cause significant morbidity and mortality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Falls are defined as unintentionally coming to the ground or some lower surface and not as a consequence of sustaining a violent blow, loss of consciousness and sudden paralysis as in a stroke incident or epileptic seizure [6]. Falls are a major problem in the elderly because they cause significant morbidity and mortality [6]. Risk of falling increases due to decrease in reaction time to external stimuli, such as changes in decubitus or shifts in gait, may be associated with changes in insulin action which lead to constant changes in blood glucose concentrations, affecting cerebral function [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation